Social capital and health consciousness based on regional differences in China: a cross-sectional study - Shi, Zhen; Du, Xixi; Wang, Dongyang; Paek, Seung Chun; Kitcharoen, Patreeya; Li, Juan; Marohabutr, Thammarat (Frontiers in Public Health, 2025)
BackgroundHealth consciousness is a critical determinant of individuals’ engagement in health behaviors, while social capital influences health-related questions. This study aims to explore the relationship between social capital-comprising social participation, social trust, social networks, and social reciprocity, and health consciousness in China, with particular emphasis on regional variations.MethodsThis study utilizes data from the 2021 Chinese Social Survey (CSS2021) and employs descriptive analysis, binary logistic regression, and subsample regression to examine the effects of social capital on health consciousness, with a focus on regional differences across China.ResultsThere are significant regional differences in health consciousness among Chinese residents. Overall, the proportion of residents exhibiting a high level of health consciousness accounted for more than half (67.3%), with eastern China leading at 68.8% and the western region at a lower level of 64.3%. Social participation, social trust, and social reciprocity were found to significantly influence health consciousness. Regionally, the eastern region was influenced by social participation, social trust, and social networks; the central region by social participation alone; and the western region by social reciprocity (p < 0.05). In terms of socio-demographic and economic characteristics, the eastern region’s health consciousness was significantly influenced by age, gender, education, family economic status, and happiness. In the central region, factors included gender, marital status, education, family economic status, recent medical experience, and social equity cognition. In the western region, marital status, education, income group, family economic status, and social insurance satisfaction were significant factors (p < 0.05).ConclusionThis study highlights significant regional disparities in health consciousness among Chinese residents with variations closely linked to socioeconomic development. Social capital, including social participation, social trust, social networks, and social reciprocity, plays a crucial role, with its impact varying across regions. Factors such as age, gender, education, income, and family economic status influence health consciousness differently depending on the region. The findings underscore the need for region-specific health policies that address socioeconomic factors and strengthen social capital, aiming to improve health consciousness and public health outcomes across China.